Prevalence and Risk Factors of Trypanosomosis in Dromedary Camels in the Pastoral Areas of the Guji Zone in Ethiopia - Gossa Alemu; Rahmeto Abebe (Journal of Parasitology Research)
Camel trypanosomosis is a life-threatening disease with adverse effects on camel health, production, and working efficiency. Despite this, camel trypanosomosis has received much less attention in Ethiopia compared with the disease in cattle and other animals. This cross-sectional study was conducted to evaluate the prevalence of camel trypanosomosis, identify the potential risk factors, and determine the importance of trypanosomosis in causing anemia in camels in the Gorodola and Liben districts in the Guji Zone of Oromia Regional State in Ethiopia. To this end, blood samples were collected from randomly selected 450 camels in heparinized capillary tubes and analyzed for the presence of Trypanosoma evansi using the buffy coat technique and Giemsa-stained thin smears. T. evansi infection was detected in 24 (5.3%) of the 450 camels examined. Out of the four variables analyzed in this study, two factors, such as body condition (BC) score and age, were found to be significantly (P<0.05) associated with trypanosomosis in camels. A higher prevalence of trypanosomosis was observed in camels in poor BC (13.22%) than in camels in good (4.62%) or moderate (1.01%) BC. Likewise, adult camels (8.09%) were infected more frequently than young camels (1.12%), whereas no trypanosomes were detected in camel calves under 2 years of age. No significant statistical difference was found between the two districts, and male and female camels (P>0.05). Statistically, the mean packed cell volume was significantly lower (P<0.05) in parasitemic camels (26.5%±7) as compared with aparasitemic camels (33.9%±9.1). In conclusion, the current study conducted during a dry season showed a moderate prevalence of trypanosomosis in camels. Further studies using more sensitive and specific diagnostic tests, such as miniature anion-exchange centrifugation technique, serology, or molecular tests, are needed to establish a true epidemiological dataset on the prevalence and seasonality of the disease and its vectors in the study area to recommend viable control measures.